50=h-3

Simple and best practice solution for 50=h-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 50=h-3 equation:


Simplifying
50 = h + -3

Reorder the terms:
50 = -3 + h

Solving
50 = -3 + h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-1h' to each side of the equation.
50 + -1h = -3 + h + -1h

Combine like terms: h + -1h = 0
50 + -1h = -3 + 0
50 + -1h = -3

Add '-50' to each side of the equation.
50 + -50 + -1h = -3 + -50

Combine like terms: 50 + -50 = 0
0 + -1h = -3 + -50
-1h = -3 + -50

Combine like terms: -3 + -50 = -53
-1h = -53

Divide each side by '-1'.
h = 53

Simplifying
h = 53

See similar equations:

| (x-10)/100=5 | | -10=5/12*n | | 8e^8t=10e^7t | | -4x^3-9x^2=0 | | 12y=15x-9 | | c+11=4c+5 | | 9n-31=6n+5 | | 2n-22=n/4 | | -9y=9y-1 | | ((y+8)*(y+8))-40=0 | | -1/5+-2=4 | | 4+3(h+1)=4h+6 | | 2.50=1201.10 | | 9-2k=11 | | -1/50+-2=4 | | 10[y+5]=10 | | 500=45x+35(12-x) | | 11-8x-4x^2=0 | | 9y=9y-15 | | 9x-2+5(x+9)=85 | | 77x+25x=400+25x | | -15x+11=86 | | 3x+6(x+5)=-51 | | 2x+200=800-22x | | 166=s+s+2+26+s | | 166=s+s+2+26s | | 10c-9=8c+5 | | 10-2(x+3)=4 | | -14+3n+30=14n+28+n | | 11m+2n+4m-n= | | (4/9)(5/18) | | 14a-4a+5a-3a= |

Equations solver categories